2006
DOI: 10.1258/rsmsmj.51.4.35
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ attitudes towards mydriasis for diabetic eye disease screening

Abstract: Many patients attending diabetic eye screening return to driving and work immediately after the appointment. Introduction of the use of routine drops may discourage attendance. Education and experience may have an important role in improving acceptability of mydriatic eye drops. Retinal screeners need to have clear guidelines with which to advise patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…For some patients and practices, the DRS programme worked well and we confirm previous findings that a convenient screening location near home was beneficial 24 and that preserving vision was prioritised among patients with diabetes. 25 We also confirm previous studies finding that for others, misunderstandings about the importance of diabetes and personal risk, 22 26 lack of DRS awareness, psychological factors, practical obstacles 22 and the deterrent side effects of mydriasis 27 represented potential attendance barriers.…”
Section: Discussionsupporting
confidence: 88%
“…For some patients and practices, the DRS programme worked well and we confirm previous findings that a convenient screening location near home was beneficial 24 and that preserving vision was prioritised among patients with diabetes. 25 We also confirm previous studies finding that for others, misunderstandings about the importance of diabetes and personal risk, 22 26 lack of DRS awareness, psychological factors, practical obstacles 22 and the deterrent side effects of mydriasis 27 represented potential attendance barriers.…”
Section: Discussionsupporting
confidence: 88%
“…In a recent study about patients' attitude towards mydriasis for diabetic eye disease, screening found that many return to work and driving immediately after the appointment and the introduction of the routine use of drops may discourage attendance [26]. There are limitations to this study that need to be considered when interpreting the results.…”
Section: Discussionmentioning
confidence: 85%
“…Seven studies were conducted in existing DRS programs (7/77, 9.1%) [64,86,87,96,97,103,107]. Nine studies were conducted at secondary level medical and diabetes clinics (9/77, 12.7%) [43,51,68,70,74,84,104,108,113].…”
Section: Resultsmentioning
confidence: 99%